Implementasi Lean Six Sigma Untuk Meningkatkan Kualitas Layanan Pada Jasa Pengiriman Barang Kargo Udara Di Terminal Kargo Bandara Soekarno-Hatta - Hartono Hartono; Achmad Al-Hafizh Destian (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2026)
Issues in air cargo delivery such as delays, damage, and failed shipments pose major challenges to maintaining service quality. To reduce the high error rate, which averaged 45.26% and far exceeded the 15% tolerance limit, the Lean Six Sigma approach was applied using the DMAIC method (Define, Measure, Analyze, Improve, Control). The Process began with problem identification in the operational area of the Soekarno-Hatta Airport Cargo Terminal during the January to June 2025 period. Analysis revealed that the main causes stemmed from human error, unstandardized work methods, and weak procedural Control. Corrective actions included the use of plastic wrapping, fragile item labeling, and strengthening of monitoring and regular evaluation systems. After implementation, a significant reduction in delivery disruptions was observed, along with an Improvement in Process Sigma levels, indicating enhanced service quality. The application of Lean Six Sigma proved effective in increasing operational efficiency and delivery reliability. These results may serve as a reference for improving air cargo logistics service systems in a sustainable manner. Keywords: Lean Six Sigma, service quality, air cargo delivery, DMAIC, Improvement